2019
DOI: 10.1002/anie.201910894
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Posttranslational Modification Reactions for the Synthesis of Ψ[CH2NH]‐Containing Peptides

Abstract: The Ψ[CH2NH] reduced amide bond is a peptide isostere widely used in the development of bioactive pseudopeptides. Reported here is a method of chemoenzymatic posttranslational modification for the synthesis of Ψ[CH2NH]‐containing peptides converted from ribosomally expressed peptides. The posttranslational conversion composed of an enzymatic cyclodehydration and facile two‐step chemical reduction achieves deoxygenation of a specific amide bond present in a nonprotected peptide in water. This method generates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In principle, by modifying the γ-substitution of the 4bromovinylglycine derivative (propyl group in BrvG), this posttranslational chemical modification reaction is potentially applicable to the synthesis of peptides bearing more diverse azole structures, though it could be limited to those with substitutions at the 5th position. More importantly, this method can be integrated with other previously devised chemical posttranslational modification reactions [62][63][64][65][66][67] to yield peptides with various non-canonical backbone structures, expanding the chemical diversity of peptidomimetics accessible by in vitro translation.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, by modifying the γ-substitution of the 4bromovinylglycine derivative (propyl group in BrvG), this posttranslational chemical modification reaction is potentially applicable to the synthesis of peptides bearing more diverse azole structures, though it could be limited to those with substitutions at the 5th position. More importantly, this method can be integrated with other previously devised chemical posttranslational modification reactions [62][63][64][65][66][67] to yield peptides with various non-canonical backbone structures, expanding the chemical diversity of peptidomimetics accessible by in vitro translation.…”
Section: Resultsmentioning
confidence: 99%
“…82 In addition, the FIT−PatD system has been further integrated with a chemical modification to generate the Ψ[CH 2 NH] reduced amide backbone (Figure 9b). 83 The Ψ[CH 2 NH] reduced amide backbone is a well-documented peptide isostere and is widely used in bioactive peptidomimetics. Chemical reduction of the backbone thiazoline moiety produced in the FIT−PatD system resulted in thiazolidine, which could be further reduced to afford a Ψ[CH 2 NH] structure.…”
Section: Fit System Integrated With Ripp Enzymes For In Vitro Biosynt...mentioning
confidence: 99%
“…In addition, the FIT–PatD system has been further integrated with a chemical modification to generate the Ψ­[CH 2 NH] reduced amide backbone (Figure b) . The Ψ­[CH 2 NH] reduced amide backbone is a well-documented peptide isostere and is widely used in bioactive peptidomimetics.…”
Section: Combination Of the Fit System With Posttranslational Modific...mentioning
confidence: 99%
“…Previous work has shown that the cyclodehydratases PatD 14 and TruD 15 support leader sequence-dependent oxazoline/thiazoline formation within substrates containing nc-⍺-AAs adjacent to 16 or at the cyclization site itself. [17][18][19] In related work, it was shown that a chimeric leader peptide could direct the cyclodehydratase LynD 15 and the dehydrogenase TbtE 20 to install thiazol(in)es within substrates containing nc-⍺-AAs adjacent to the cyclization site. 21 Finally, reconstituted lactazole biosynthesis, 22 including the cyclodehydratase-dehydrogenase pair LazDE/LazF, was found to install oxazoles and thiazoles within polypeptide substrates containing ⍺-hydroxy, N-methyl, cyclic ⍺-, and β 3 -amino acids 23 at sites distal from the site of heterocyclization (> 4 residues away).…”
Section: Introductionmentioning
confidence: 99%